The radiology handbook : a pocket guide to medical imaging - Benseler, J. S., 1954- (White coat pocket guide., 2006)
Designed for busy medical students, The Radiology Handbook is a quick and easy reference for any practitioner who needs information on ordering or interpreting images. The book is divided into three parts: - Part I presents a table, organized from head to toe, with recommended imaging tests for common clinical conditions. - Part II is organized in a question and answer format that covers the following topics: how each major imaging modality works to create an image; what the basic precepts of image interpretation in each body system are; and where to find.